Grapevine holobiome metatranscriptomics provides a glimpse into the wood mycovirome - Debat, Humberto Julio; Paolinelli, Marcos; Escoriaza, Maria Georgina; Garcia Lampasona, Sandra Claudia; Gomez Talquenca, Gonzalo; Bejerman, Nicolas Esteban (Elsevier, 2025)
Given the agronomic and economic importance of viticulture, grapevine has been shown to host the largest number of viruses among plants to date. Nevertheless, studies assessing the grapevine-associated holobiont remain scarce. In this context, the viral component of this ecological niche is understudied. In this work, through metatranscriptomics of wood samples from individual grapevines that were either healthy or exhibited symptoms of grapevine trunk disease from Argentina, we provide a glimpse into the wood linked virome. Virus discovery from high-throughput sequencing data resulted in the identification and reconstruction of 123 novel virus sequences. Genetic and phylogenetic insights suggest that these sequences correspond to 78 novel virus species. Structural and functional annotation of the viruses showed a great diversity of genomic organizations, with the presence of dsRNA, ssRNA( ) and ssRNA(+) viruses belonging to more than 15 virus families. Some highly divergent viruses resembling narnaviruses, ophioviruses, deltaflexiviruses and bunyaviruses could be accommodated within new genera or even new virus families. The differential detection and variable RNA levels across samples suggest complex dynamics and prevalence patterns of those novel viruses. The viral profile described here provides a first insight into the multifaceted South American grapevine wood holobiont mycovirome.